A meta-analysis of the association between post-traumatic stress disorder and cancer risk - Yang, Juanjuan; Jiang, Wei (Frontiers in Psychiatry, 2023)
Several studies have investigated the link between post-traumatic stress disorder (PTSD) and cancer risk but reported mixed results. The objective of our study was to investigate the association between PTSD and cancer risk.Studies published in English about the relationship between PTSD and cancer incidence were systematically searched. We performed a meta-analysis to estimate the relative risks (RR) and 95% confidence intervals (CI) for cancer incidence.A total of 3129 articles were screened. Finally, 8 articles and 11 studies were included in the meta-analysis. We found that PTSD was not associated with cancer risk compared with controls.For site-specific cancer, our results showed that women with PTSD were associated with higher risk of ovarian cancer than controls. However, PTSD was not associated with the risk of gastrointestinal cancer, breast cancer and lung cancer.These analyses based on studies published in English suggest that PTSD is associated with ovarian cancer risk, although the evidence base is very limited. Future studies are needed to investigate the mechanisms that PTSD diagnosis influenced cancer incidence depending on types of cancer.